The Causes of the Astrakhan Campaign of 1569 - Marina Maratovna Imasheva, Dina Abdulbarovna Mustafina, Dmitriy Maratovich Yakupov,; Rail Ravilovich Fakhrutdinov, Marat Salavatovich Gatin, Lenar Fargatovich Abzalov, (Opción, 2019)
The study aims to investigate the causes of the Astrakhan campaign of 1569 via the historical-genetic method in combination with a systematic approach and system analysis. The research showed that the active policy in the third quarter of the XVI century, on the one hand, led to the approval of the Moscow state at the estuary of Volga and strengthening of its position in the North Caucasus. In conclusion, the clash of political, economic and ideological interests of the Ottoman Empire, the Polish-Lithuanian state, the Crimean Khanate and the Moscow State led to the outbreak of a military conflict.